If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying -272 = 3n + -7(8n + 1) Reorder the terms: -272 = 3n + -7(1 + 8n) -272 = 3n + (1 * -7 + 8n * -7) -272 = 3n + (-7 + -56n) Reorder the terms: -272 = -7 + 3n + -56n Combine like terms: 3n + -56n = -53n -272 = -7 + -53n Solving -272 = -7 + -53n Solving for variable 'n'. Move all terms containing n to the left, all other terms to the right. Add '53n' to each side of the equation. -272 + 53n = -7 + -53n + 53n Combine like terms: -53n + 53n = 0 -272 + 53n = -7 + 0 -272 + 53n = -7 Add '272' to each side of the equation. -272 + 272 + 53n = -7 + 272 Combine like terms: -272 + 272 = 0 0 + 53n = -7 + 272 53n = -7 + 272 Combine like terms: -7 + 272 = 265 53n = 265 Divide each side by '53'. n = 5 Simplifying n = 5
| 0.7z-3=0 | | 3.5+46.9*x-9.8*x^2=0 | | 6+3x=8+11 | | 1404=.02(x) | | 14M-28=4(M+3) | | 3y=28-4y | | X/3=x-31/2 | | (3x^5-2x^3+4)+(x^4+2x^3-7)= | | 2y-2/5=-1/3 | | 8(3a+6)=9(2a-3)-9 | | 5-(2x+4)=15 | | -8(-x-7)=-x+29 | | 24y-20x=72 | | 1404=.08(x)+.04(y) | | 4(x+1)=2(x+3)-4 | | Z^2=8+6i | | 11-w=187 | | 4x+1=3(x+2)+2x | | 20.44=1.5x*x | | 2n^2+3x-9=0 | | 20x-5y=1.2 | | 0=1.5x*x | | 2/3x-5=61 | | 672=.08(x) | | 5-3(2x+2)=1-7x | | 1200-1/6 | | 5(x+3)=3x+35 | | 8r-28=6(3r+7) | | b^2=-5b | | 10g+2=2g+102 | | 6(z-4)=30 | | 3412x=18 |